A potential role of Sirtuin3 and its target enzyme activities in patients with ovarian endometrioma. (2nd November 2021) - Kaleler, İslim and Acikgoz, Abdullah Serdar and Gezer, Altay and Uslu, Ezel
Abstract: Objective: Sirtuin3 (SIRT3) is a NAD + -dependent major mitochondrial deacetylase. In this study, we aimed to investigate SIRT3 levels and their target enzyme activities, including glutamate dehydrogenase (GDH), succinate dehydrogenase (SDH), and manganese superoxide dismutase (MnSOD), also to determine the antioxidant capacity and oxidative stress in tissue, mitochondria and serum samples in ovarian endometrioma patients. Methods: We collected serum and endometrioma tissue samples from 30 patients. In the control group, we collected serum and eutopic endometrial tissue samples from 26 women without endometriosis. Results: SIRT3 levels were significantly decreased in endometrioma tissue samples compared to the control group. There was no statistically significant difference in SIRT3 levels between patient and control serum samples. Furthermore, there was a decrease in GDH and SDH enzyme activities in both endometrioma tissue homogenate and mitochondria. MnSOD activity was decreased in tissue homogenate but increased in mitochondria and there was no difference in serum. While total SOD activity was decreased, CuZnSOD activity was increased in both tissue and serum samples. Besides these, total antioxidant capacity and advanced oxidation protein products (AOPP) levels were decreased in endometrioma tissue and mitochondria, but there was no difference in serum. Conclusions: Our results suggested that decreased levels of SIRT3 in endometrioma may be an important factor in the weakening of mitochondrial energy metabolism and antioxidant defense in endometriosis. We think that SIRT3 deficiency may be an important factor underlying the pathogenesis of endometriosis. More detailed studies are needed to reveal the relationship between SIRT3 and metabolism and oxidative stress in ovarian endometrioma.